Peran Kepemilikan Institusional Sebagai Pemoderasi Pada Determinan Fraudulent Financial Statement: Analisis Fraud Diamond Model - Nabila Jasmine, Adinda; Prajanto, Agung; Dapit Pamungkas, Imang; Minarso, Bambang (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
This study employs a fraud diamond model analysis that consists of four factors: pressure, opportunity, rationalization, and capability to examine and analyze those effects on fraudulent financial statements, with institutional ownership as a moderating variable. Purposive sampling was used to choose the study`s sample, which consists of state-owned enterprises (BUMN) that meet the requirements. Regression analysis was employed as an analytical method using a quantitative approach, and this study contained 96 samples. WarpPLS version 8.0 software was used to help with the statistical data analysis needed to test the hypothesis. This study found that pressure, opportunity, and rationalization have a positive effect on fraudulent financial statements, while capability has no effect on fraudulent financial statements. In addition, institutional ownership is able to moderate the relationship between pressure on fraudulent financial statements and opportunity on fraudulent financial statements.